Structure of Independent Clauses in Balantak Language - Madjid, Rifki Julyanto; Idris; Saputra , Gusti Ketut Alit; Syamsuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The main objective of this study is to explain the independent clause of Balantak language. This research is qualitative research with descriptive method. The data source of this study is based on interviews with the Mamping village community. Data were collected using Sudaryanto's theory (1993), namely the simik and katat techniques. To analyze the data in this study, the researcher used the equivalent and distributional methods. The results of this study found three internal structures of Balantak language, namely intransitive clauses, transitive clauses, and equative clauses. Balantak language clauses consist of three core constituents, namely subject, predicate, and object.